Analisis Kebijakan Laku Pandai Terhadap Pengembangan Ekonomi Lokal di Sumatera Barat - Robi Eka Putra; Roni Ekha Putera; Desna Aromatica (Journal of Social and Policy Issues, 2023)
The Laku Pandai policy that has been issued by the Government is expected to increase the level of financial inclusion and literacy in Indonesia. However, not many realize that the Laku Pandai policy also has a further impact on local economic development in the region. Therefore, this study aims to analyze Laku Pandai's policy on local economic development in West Sumatra. This study was designed using a qualitative method with a descriptive approach. The source of the data used is from interviews with Laku Pandai agents, in this case BRILink agents in Padang City and Solok Regency as representatives of urban, sub-urban and rural areas in West Sumatra. The results show that the Laku Pandai policy issued by the government has an influence on local economic development, especially in West Sumatra. This can be seen from the important role of local economic development that can be seen after the implementation of the BRIlink Agent began in 2016. Important roles that can be seen and felt such as increasing business opportunities, employment, business retention, economic diversification, self-sufficiency, increasing the tax base from the world business and society, quality of life, recognition of local products, and increased competitiveness. All of these important roles are certainly not only felt by BRILink agents, but also by all parties and layers in the area where the agent is located.